Peran E-Service Quality, Kemudahan, Kepuasan dalam Membentuk Niat Beli Ulang Konsumen Lazada - Dwicahyanto, Dhimas Bagus (Jurnal Ilmu Manajemen, 2020)
Lazada is a market leader of e-commerce in Shout-East Asia. This study aims to analyze and discuss the effect of the e-service quality and eases on the repurchase intention through satisfaction. This study uses college students aged 18-25 years as respondents, which have purchased Lazada at least once, and their last purchase is in the last one month. The sampling method is non-probability sampling using a snowball sampling technique. The number of samples is 220 respondents. Data were collected by an online questionnaire and analyzed using AMOS. The result of this study indicates that e-service quality and ease have a significant effect on satisfaction and repurchase intention.